2020
DOI: 10.1016/j.jcin.2020.01.219
|View full text |Cite
|
Sign up to set email alerts
|

Routine CYP2C19 Genotyping to Adjust Thienopyridine Treatment After Primary PCI for STEMI

Abstract: @DrHulot_PARCC Anti-platelet therapy adjustment guided by CYP2C19 genotyping can be done in <7 days in STEMI patients with saliva DNA analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 35 publications
0
23
0
Order By: Relevance
“…The data from real-world observations 43 demonstrated a higher risk for cardiovascular events in patients with a CYP2C19 LOF allele who received clopidogrel than in those who received an alternative therapy. The GIANT (NCT01134380) study 44 showed a similar outcome, and thus it was vital to verify the potential benefit of the genotype-guided personalized test. To date, four meta-analyses on genotype-guided antiplatelet therapy versus conventional antiplatelet treatment have been conducted, [18][19][20][21] yielding different conclusions.…”
Section: The Conclusion Was Not Based Solely On High-quality Evidencementioning
confidence: 99%
“…The data from real-world observations 43 demonstrated a higher risk for cardiovascular events in patients with a CYP2C19 LOF allele who received clopidogrel than in those who received an alternative therapy. The GIANT (NCT01134380) study 44 showed a similar outcome, and thus it was vital to verify the potential benefit of the genotype-guided personalized test. To date, four meta-analyses on genotype-guided antiplatelet therapy versus conventional antiplatelet treatment have been conducted, [18][19][20][21] yielding different conclusions.…”
Section: The Conclusion Was Not Based Solely On High-quality Evidencementioning
confidence: 99%
“…Examples of alternative approaches to evidence generation include pragmatic trials and observational studies of patients receiving testing as part of clinical care. Similar to RCTs, many pragmatic and observational studies to date have demonstrated improved outcomes with a pharmacogenetic‐guided approach 50–55 . Data from additional pragmatic trials are forthcoming from efforts, such as from the Implementing GeNomics In pracTicE (IGNITE) Pragmatic Trials Network (ClinicalTrials.gov Identifier: NCT04445792) and the Ubiquitous Pharmacogenomics Consortium 4 .…”
Section: Types Of Pharmacogenetic Evidence and Their Limitationsmentioning
confidence: 99%
“…Because of CYP2C19 genetic polymorphism, the response of clopidogrel differs widely among patients. Previous studies showed that adjusting thienopyridine treatment in patients after primary percutaneous coronary intervention for ST-Elevation Myocardial Infarction, according to the CYP2C19 genotype, can improve a patient's outcome [31,32]. Whether adjusting the clopidogrel dose after CYP2C19 genotyping in stroke patients can reduce recurrent stroke risk needs further investigation.…”
Section: Plos Onementioning
confidence: 99%